2005
DOI: 10.1093/jn/135.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry (Morus alba L.) Leaves and Their Major Flavonol Quercetin 3-(6-Malonylglucoside) Attenuate Atherosclerotic Lesion Development in LDL Receptor-Deficient Mice

Abstract: The effects of dietary consumption of mulberry (Morus alba L.) leaves and their major flavonol glycoside, quercetin 3-(6-malonylglucoside) (Q3MG), on the development of atherosclerotic lesions, in relation to the susceptibility of plasma LDL to oxidative modification, was studied in LDL receptor-deficient (LDLR-/-) mice. Male mice aged 8 wk were randomly assigned to 4 groups (control, quercetin, Q3MG, and mulberry). The control group was fed an atherogenic-diet containing 3 g cholesterol and 15 g cocoa butter/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
119
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(132 citation statements)
references
References 43 publications
10
119
1
2
Order By: Relevance
“…Blood glucose and insulin levels are also important for preventing oxidative stress in intravascular endothelial cells, and atherosclerosis. LEM has demonstrated a suppressive effect on atherosclerotic lesions in mice [7] and the protective effect on vascular system through the decreasing of oxidative stress and anti-glycation [18][19][20], suggesting that it should form part of the dietary therapy for type 1 and 2 diabetes mellitus, and for other metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood glucose and insulin levels are also important for preventing oxidative stress in intravascular endothelial cells, and atherosclerosis. LEM has demonstrated a suppressive effect on atherosclerotic lesions in mice [7] and the protective effect on vascular system through the decreasing of oxidative stress and anti-glycation [18][19][20], suggesting that it should form part of the dietary therapy for type 1 and 2 diabetes mellitus, and for other metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the appearance of polyuria and the elevation of fasting blood glucose and insulin were delayed by the daily intake of LEM in diabetic mice [5]. LEM has also been reported to have other physiological effects, including the inhibition of low-density lipoprotein oxidation in vitro [6], and the attenuation of atherosclerotic lesion development in mice [7]. We previously clarified that confections containing LEM suppressed postprandial elevations of glucose and insulin in healthy subjects [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mulberry extract contains compounds such as fagomine, which induces insulin secretion (17), and antioxidants that putatively reduce lipid peroxidation (5, 18,19).…”
Section: Research Design and Methods -Participants Includedmentioning
confidence: 99%
“…Odbayar et al (2006) reported that dietary quercetin but not rutin reduced serum cholesterol and phospholipid levels in ICR mice, and that quercetin inhibited the expression of various kinds of mRNA related to fatty acid synthesis. On the other hand, Enkhmaa et al (2005) reported that dietary quercetin (50 mg/100 g) had no significant beneficial effects on plasma total cholesterol, LDL cholesterol and triglyceride levels of LDL receptor-deficient mice fed an atherogenic-diet containing cholesterol. In addition, it was shown that plasma cholesterol levels were not reduced by dietary quercetin (1% in diet) in mice fed a high-cholesterol diet or in Watanabe heritable hyperlipidemic rabbits (Lauridsen and Mortensen, 1999).…”
Section: Discussionmentioning
confidence: 99%